Low pre-season hamstring-to-quadriceps strength ratio identified in players who further sustained in-season hamstring strain injuries: A retrospective study from a Brazilian Serie A team - Veeck, F.; Ruas, C. V.; Pinto, M. D.; Grazioli, R.; Cardoso, G. P.; Albuquerque, T.; Schipper, L.; Valente, H. G.; Santos, V. H.; Dornelles, M.; Rabaldo, P.; Rocha, C. S.; et al. (Sports, 2023)
A common pre-season injury prevention assessment conducted by professional football clubs is the hamstring-to-quadriceps (H:Q) strength ratio calculated by peak torque (PT). However, it is debatable whether players that present low pre-season H:Q ratios are more susceptible to further sustaining in-season hamstring strain injuries (HSI). Based upon retrospective data from a Brazilian Serie A football squad, a particular season came to our attention as ten out of seventeen (~59%) professional male football players sustained HSI. Therefore, we examined the pre-season H:Q ratios of these players. H:Q conventional (CR) and functional (FR) ratios, and the respective knee extensor/flexor PT from the limbs of players further sustaining in-season HSI (injured players, IP) were compared to the proportional number of dominant/non-dominant limbs from uninjured players (UP) in the squad. FR and CR were ~18-22% lower (p < 0.01), whereas quadriceps concentric PT was ~25% greater for IP than UP (p = 0.002). Low scores of FR and CR were correlated (p < 0.01) with high levels of quadriceps concentric PT (r = -0.66 to -0.77). In conclusion, players who sustained in-season HSI had lower pre-season FR and CR compared to UP, which appears to be associated with higher levels of quadriceps concentric torque than hamstring concentric or eccentric torque.